2018
DOI: 10.3390/en11040800
|View full text |Cite
|
Sign up to set email alerts
|

A Generalised Assessment of Working Fluids and Radial Turbines for Non-Recuperated Subcritical Organic Rankine Cycles

Abstract: The aim of this paper is to conduct a generalised assessment of both optimal working fluids and radial turbine designs for small-scale organic Rankine cycle (ORC) systems across a range of heat-source temperatures. The former has been achieved by coupling a thermodynamic model of subcritical, non-recperated cycles with the Peng-Robinson equation of state, and optimising the working-fluid and cycle parameters for heat-source temperatures ranging between 80 • C and 360 • C. The critical temperature of the workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
(50 reference statements)
1
16
0
Order By: Relevance
“…and by allowing p r to take values both above and below unity, and ε to vary between 0 and 1, it is possible to evaluate subcritical and transcritical cycles with or without recuperation. The validity of the ORC model for non-recuperated, subcritical cycles, based on the Peng-Robinson equation of state, has previously been confirmed by the authors (White and Sayma, 2018). It was observed that the optimal cycle parameters identified from the model were the same as those identified using an ORC model based on REFPROP, with the maximum deviation in the power output being <6%.…”
Section: Thermodynamic Orc Modelmentioning
confidence: 58%
See 3 more Smart Citations
“…and by allowing p r to take values both above and below unity, and ε to vary between 0 and 1, it is possible to evaluate subcritical and transcritical cycles with or without recuperation. The validity of the ORC model for non-recuperated, subcritical cycles, based on the Peng-Robinson equation of state, has previously been confirmed by the authors (White and Sayma, 2018). It was observed that the optimal cycle parameters identified from the model were the same as those identified using an ORC model based on REFPROP, with the maximum deviation in the power output being <6%.…”
Section: Thermodynamic Orc Modelmentioning
confidence: 58%
“…where the coefficients A, B, and C are constants that control the shape of the fluid's saturation dome, and thus whether the fluid has a saturated vapor line with a positive or negative gradient and is categorized as dry or wet, respectively. This has been demonstrated in our previous study (White and Sayma, 2018). Using Equations (1, 2) all of the required properties to analyse the thermodynamic cycle, namely the specific enthalpy h in J/mol, the specific entropy s in J/(mol K), and the specific volume v = 1/ρ in m 3 /mol, can be determined based on a vector of six fluid parameters:…”
Section: Peng-robinson Equation Of Statementioning
confidence: 91%
See 2 more Smart Citations
“…The efficiency was also increased from 10.5% for the single-stage turbine to 14.2% for the two-stage turbine. A generalized assessment of both optimal working fluids and radial turbine designs for a small-scale organic Rankine cycle was done by [25], using the Peng-Robinson equation of state to optimize the working fluid and cycle parameters in the temperature range of 80 to 360 • C. A correlation has been deduced which relates the heat source temperature to the critical temperature of the working fluid, which can be used to find the optimum working fluid for a given temperature. Using zeotropic mixtures of working fluids in an ORC will increase the performance of the ORC.…”
Section: Introductionmentioning
confidence: 99%